Evaluating the effectiveness of sugarcane waste biochar in the purification of greywater - Mugambi, Victor; Too, Vitalis; Mungai, George N. (African Journal of Science, Technology and Social Sciences, 2025)
The study investigated effectiveness of sugarcane waste biochar as a sustainable material for purifying greywater to address environmental pollution and enhance water recycling. Biochar was produced by heating sugarcane waste at 500°C, with half of it activated using potassium hydroxide to enhance adsorption. X-ray fluorescence, X-ray diffraction and Fourier transform infrared spectroscopy were used to characterise the biochar structure. Greywater samples obtained from the kitchen, bathroom and carwash were purified by filtering 100 mL of samples through 10 g of biochar for 5 minutes. The activated and inactivated biochar achieved 92–96% and 80–87% removal efficiency of lead (II) ions, respectively. Chromium (VI) ions removal ranged from 84–92% and 82–86% with activated and inactivated biochar, respectively. Activated biochar removed 76–77% of oil and grease compared to 51–57% for inactivated biochar. Both biochar increased the pH levels, with activated biochar causing a more rise by 63–73%. Total suspended solids removal efficiencies were 21–34% and 40–54% in inactivated and activated biochar, respectively. Slight decrease in sodium dodecyl sulphate detergent, electrical conductivity and total dissolved solids was observed for both biochar. There was significant difference between the purification efficiency of inactivated and activated biochar shown by the |t| statistic values which were above t4 critical value of 2.78 (P = 0.05). Based on the study findings, activated sugarcane biochar was reliable for greywater treatment, especially the removal of heavy metal pollutants, oil and grease.